O-223 Latest development of IVM in assisted reproduction. (30th June 2022) - Ho, T; Le, A; Vuong, L
Abstract: Latest development of IVM in assisted reproduction In vitro maturation (IVM) is an assisted reproductive technology involving collection of immature cumulus-oocyte complexes at the prophase I stage, which are then matured to the metaphase II stage in vitro . IVM has several advantages over IVF, including negligible risk of ovarian hyperstimulation syndrome, lower medication costs, and patient convenience. Given that IVM can be done within a relatively short time frame without the need for ovarian stimulation, it is particularly useful for fertility preservation in patients with cancer who are unable to delay chemotherapy, or in women with breast cancer for whom exposure to elevated estradiol concentrations may accelerate their disease. The European Society of Human Reproduction and Embryology (ESHRE) Guideline on Female Fertility Preservation published in 2020 suggested IVM as a fertility preservation technique. The Practice Committees of ASRM in 2021 published the document that presented an overview of published evidence supporting the conclusion that IVM should no longer be considered an experimental technique. The potential for wider clinical application of IVM was suggested. Patient populations particularly suited to the use of IVM include women with polycystic ovaries, have higher risk of ovarian hyperstimulation syndrome, and those requiring fertility preservation. During the last two decades, IVM has been utilized for patients with PCOS to reduce the health risks associated with ovarian hyperstimulation syndrome, for fertility preservation, or just as an alternative, more user-friendly approach to ART. The effectiveness of IVM relies on successful synchronization of meiotic and cytoplasmic maturation of oocytes. Efforts to improve the efficacy of IVM have included the use of new IVM culture systems, aimed at enhancing the competence of IVM oocytes. Recently, the use of oocyte prematuration (or pre-IVM) culture systems to prevent spontaneous in vitro maturation processes and maintain cumulus-oocyte gap junctional communication have been described in humans. Over the last five years, a new biphasic IVM culture system has been developed to improve the efficacy of IVM. Recent promising data from this new IVM culture system, called capacitation (CAPA) IVM, showed promising results. CAPA-IVM involves successfully maturing oocytes from small 2–8 mm follicles with no hCG injected prior to oocyte retrieval. Recently, a large RCT compared the efficacy of CAPA IVM and conventional IVF/ICSI in women with PCO showed that CAPA (biphasic) IVM was non-inferior to IVF in term of live birth rate after the first embryo transfer. One of the concerns regarding IVM is the health of babies after utilization of this procedure. Based on currently available data, IVM appears to be safe from a neonatal health and childhood development perspective. There is still room for further development of more efficient IVM protocols (89). Recent knowledge about oocyte physiology and development can be translated into clinical practice to improve the efficacy of these protocols. There are several reasons why all major modern ART centers should have IVM facilities and protocols available. These include the likelihood of wider application of IVM in the future, the requirement to manage indications where IVM is the only option (e.g. fertility preservation, GROS), the increasing need for more patient-friendly ART treatment, and the fact that IVM protocols are improving thanks to advances in knowledge on human follicular and oocyte development.